Preparation, Characterization and Antibacterial Efficiency of Olive Leaves Extract and Chitosan-Silver Nanoparticles using Electrochemical Method - Ahmed, Moustafa Tawfik (JOURNAL OF ADVANCES IN PHYSICS, 2019)
The present work involves the improvement of chitosan-olive leaves extract and silver nanoparticles (Cs-OLE-AgNPs) using electrochemical approach followed by UV-irradiation reduction. The formation of silver nanoparticles (AgNPs) was characterized via UV–vis spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), differential scanning calorimetry (DSC), EDX, thermal gravimetric analysis (TGA) and Swelling. The obtained nanoparticles average size was 36.19 nm. UV Spectroscopy show increase of peaks at 320 and 345 nm indicate the formation of a large cluster of AgNPs. Cs-OLE and Cs-OLE-AgNPs also demon started a relativity high antibacterial against both Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) bacteria. AgNPs show broadspectrum antibacterial activity at lower concentration (0.56%) and may be regarded as a good alternative therapeutic approach in the future.